KNOWLEDGE, ATTITUDES AND PRACTICES OF LOW-SALT DIET OF HYPERTENSIVE PATIENTS AT TUE TINH HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the current state of knowledge and attitude of salt reduction diet practices of hypertensive patients at Tue Tinh Hospital in 2025Subjects and methods: A cross-sectional descriptive study of 140 patients who came for examination and treatment at Tue Tinh Hospital who were diagnosed with hypertension during the period from January 2025 to April 2025Results: Among 140 hypertensive patients, 82.9% knew that table salt affected hypertension, 78.6% knew that instant noodles, ready-to-eat products and pickled foods with high salt content. Attitudes: 54.3% believe that reducing salt intake will support blood pressure control and improve health status; 75% are willing or very willing to change their diet to reduce salt intake. Regarding dietary practice: 52.9% always add dipping sauce; 69.3% do not have the habit of checking food labels when buying processed products. 16.4% of patients have the habit of always using salted products.Conclusion: 55% of hypertensive patients who come to Tue Tinh Hospital for examination and treatment have knowledge about the salt-reducing diet, 72.1% have a positive attitude towards reducing salt in the diet, but only 35.7% are practicing a salt-reducing diet
Keywords: Salt reduction diet, hypertensive patients, Tue Tinh Hospital.